Literasi Keuangan dan Pengelolaan Dana terhadap Motivasi Berwirausaha pada UMKM - Muhammad Rizal Saragih; Mawardi Nurullah; Rusdi Rusdi; Prima Sadewa; Sujarwo Sujarwo (Abdimisi, 2020)
The purpose of community service is to provide knowledge, and understanding of financial literacy, fund management, and increasing the spirit of entrepreneurship so as to create new jobs. The method of community service is seminars and discussions. The population in this community service activity is as many as 50 UMKM that are incorporated in the fostered PT. ASTRA Insurance in the South Jakarta area. The result of community service is that all participants can manage their business funds well, understand the status of business ownership, and be motivated in entrepreneurship so as to create new jobs.